Mindfulness Training in Improving Resilience in People with Heart Disease - Pamuji, Alta Aviva; Moordiningsih, Moordiningsih (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2021)
This study was conducted to see the effectiveness of mindfulness training to increase resilience in people with heart disease. The heart patients involved in the study were undergoing treatment and diagnosed within the past year. Subjects were divided into experimental group (n= 2) and control group (n= 2). The research design used was a pretest-posttest control group design and was measured three times (pre-test, post-test, and follow-up for one week). The measuring instrument used to measure resilience is the Resilience Scale. Mindfulness training is an intervention that includes cognitive, affective, behavioral, moral, and interpersonal aspects. Mindfulness training has been shown to have many benefits, including reducing stress, anxiety, depression, then increasing optimism, emotion regulation, self-esteem, self-confidence, and increasing empathy. The results showed significant changes after being given Mindfulness training in the experimental group (Sig = 0.042; p < 0.05), and in the experimental group, both pretest-posttest and follow-up showed significant changes.